A Lower Ordovician geomagnetic pole from Pennsylvania (Dataset) ... - Hower, James C. (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: A Lower Ordovician geomagnetic pole from Pennsylvania ...